Pengecoran Pulley Besi Cor Diameter 4”, Panjang Hub 80mm, lubang poros 18mm, Kapasitas 5 Biji/Jam - Muhammad Arsyad Almahalli; Syamsul Hadi; Muhammad Dary Alwan Zain; Ibra Hasyim Sanjaya; Fadio Priashabi (International Forum of Researchers and Lecturers, 2026)
The cracking of gray cast iron castings in the form of pulleys can result in eroding the contact surface on the V-belt in its operation as a problem faced. The purpose of casting is to obtain a 4” diameter cast iron pulley, 40 mm thick pulley, 80 mm hub length, 18 mm axle hole, 50 mm hub diameter, and 72 mm inner diameter of the pulley belt groove. The casting method includes: design of a 4” diameter pulley with a hub length of 80 mm; making a sand mold without a core; drying the mold at 200oC; preparation of casting materials-equipment; melting cast iron up to 1,350oC with the addition of 10% scrap cast iron; casting molten metal into the sand mold; dismantling the casting, cutting the pouring bowl channel and riser; drilling an 18 mm diameter axle hole; turning the V-belt groove at a 38o angle with a depth of 15 mm; finishing; and quality-dimension-defect inspection. The casting results are cast iron pulleys with a diameter of 4”, pulley thickness of 40 mm, hub length-diameter of 80-50 mm, axle hole of 18 mm, inner diameter of the pulley belt groove of 72 mm without any cavity defects or cracks, total casting cost of IDR 100,000,-/unit and process duration of 6 minutes/unit which implies that the cast iron pulley can be used with a V-section rubber belt with a smooth contact surface.